2020
DOI: 10.1515/nanoph-2019-0400
|View full text |Cite
|
Sign up to set email alerts
|

Wideband tunable perfect absorption of graphene plasmons via attenuated total reflection in Otto prism configuration

Abstract: A strategy is proposed to achieve wideband tunable perfect plasmonic absorption in graphene nanoribbons by employing attenuated total refraction (ATR) in Otto prism configuration. In this configuration, the Otto prism with a deep-subwavelength dielectric spacer is used to generate tunneling evanescent waves to excite localized plasmons in graphene nanoribbons. The influence of the configuration parameters on the absorption spectra of graphene plasmons is studied systematically, and the key finding is that perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…In the THz and IR regions, however, high quality graphene may show strong interaction with light thanks to generation of surface plasmon polaritons (SPPs), making graphene a promising alternative to typical plasmonic materials [ 22 , 23 , 24 , 25 ]. This is thanks to the capability of graphene to support plasmon modes with extremely tight confinement, long lifetime, and low losses at IR and THz frequencies [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the THz and IR regions, however, high quality graphene may show strong interaction with light thanks to generation of surface plasmon polaritons (SPPs), making graphene a promising alternative to typical plasmonic materials [ 22 , 23 , 24 , 25 ]. This is thanks to the capability of graphene to support plasmon modes with extremely tight confinement, long lifetime, and low losses at IR and THz frequencies [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the electromagnetic field intensity is inversely proportional to the distance parameter, which means that the effective SERS signal is generated on the premise that the molecule is located in the confined area around the plasmonic material [10]. Various types of SERS substrate structures ranging from nanoparticle (NP) aggregates [11][12][13][14][15], multidimensional structure [16][17][18][19][20] and composite substrate [21][22][23][24][25][26][27][28][29] were prepared to explore the better enhancement factor (EF) under various conditions. Among them, the cavity system has been paid more and more attention because of its unique light trapping characteristics [30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, graphene, [ 13 ] the truly two‐dimensional (2D) crystals consisted of carbon atoms in a honeycomb lattice, has been demonstrated to support tightly field confined plasmonic modes in the IR region, [ 14–21 ] with the dimensions of mode volumes several orders smaller than the excitation wavelengths. Particularly, such plasmonic responses can be actively tuned by an external gating voltage, [ 22–31 ] a feature that is not available in traditional metallic surface plasmons, which could enable selective enhancements of molecular infrared vibrational fingerprints. [ 32–34 ] These unprecedented properties of graphene plasmons are promising for the realization of sensitive and wideband SEIRAS in ultra‐compact sizes.…”
Section: Introductionmentioning
confidence: 99%